2020
DOI: 10.3389/fcell.2020.00554
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Exosomes From Tick Saliva and Salivary Glands Reveals Therapeutic Roles for CXCL12 and IL-8 in Wound Healing at the Tick–Human Skin Interface

Abstract: Ticks secrete various anti-coagulatory, anti-vasoconstrictory, anti-inflammatory, and anti-platelet aggregation factors in their saliva at the bite site during feeding to evade host immunological surveillance and responses. For the first time, we report successful isolation of exosomes (small membrane-bound extracellular signaling vesicles) from saliva and salivary glands of partially fed or unfed ixodid ticks. Our data showed a novel role of these in vivo exosomes in the inhibition of wound healing via downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 81 publications
(243 reference statements)
1
54
0
Order By: Relevance
“…Extracellular vesicles are small lipid blebs that secrete for cell-to-cell communication. Extracellular vesicles have been detected in the saliva of I. scapularis, Amblyomma maculatum, and H. longicornis [145][146][147]. Vesicles from H. longicornis contain known protein effectors, like lipocalins, cement-like proteins, and serpins as well as novel miRNAs suspected to influence host immune responses [145,146].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular vesicles are small lipid blebs that secrete for cell-to-cell communication. Extracellular vesicles have been detected in the saliva of I. scapularis, Amblyomma maculatum, and H. longicornis [145][146][147]. Vesicles from H. longicornis contain known protein effectors, like lipocalins, cement-like proteins, and serpins as well as novel miRNAs suspected to influence host immune responses [145,146].…”
Section: Discussionmentioning
confidence: 99%
“…Vesicles from H. longicornis contain known protein effectors, like lipocalins, cement-like proteins, and serpins as well as novel miRNAs suspected to influence host immune responses [145,146]. Furthermore, in vitro experiments indicate that vesicles from I. scapularis and A. maculatum diminish chemokine and cytokine secretion and delay wound healing responses [147]. Several studies have shown their immunomodulating effects and influence on infection by several vector-borne pathogens [148], including the transmission of Langat virus (LGTV) from tick cells to mammalian cells [149].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained for CE was comparable to that of the standard sucralfate showing increased percentage of wound closure and reduced time for complete epithelialization. This reduced duration for wound healing can be due to the release of one of the inflammatory chemokineinterleukin-8 that plays a significant role in the recruitment of inflammatory cells such as keratinocytes and fibroblasts 26 . This in turn leads to an elevation in the intracellular communication within the fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are different in origin, size, and content and involved in the pathogenesis of infection [ 9 ]. Studies performed over the past years proved that exosomes exist in almost all biological fluids [ 10 , 11 ], including plasma [ 12 , 13 ], serum [ 14 ], bovine and human milk [ 15 ], urine [ 16 ], and saliva [ 17 ]. Importantly, an increasing evidence suggests that exosomes play critical role in cell-to-cell communication [ 18 , 19 ], including the interaction between microorganisms and infected human cells.…”
Section: Introductionmentioning
confidence: 99%